A Case of Suspected Hyperphenylalaninemia at Newborn Screening by Tandem Mass Spectrometry during Total Parenteral Nutrition - Pieragostino, Damiana (Metabolites, 2020)
Phenylketonuria (PKU) is a rare autosomal recessive condition affecting about 1 in 10,000 people in the Europe, with a higher rate in some countries, like Ireland and Italy. In Italy, newborn screening (NBS) by MS/MS allows the diagnostic suspicion of PKU and its variants (Hyperphenylalaninemia (HPA), Tetrahydrobiopterin (BH4) synthesis deficiency, and Tetrahydrobiopterin (BH4) recycling deficiency) through the quantification of Phenylalanine (Phe) and the Phenylalanine/Tyrosine (Phe/Tyr) ratio in dried blood Spot (DBS) samples. Here, we report a case of an HPA whose suspicion was possible with expanded NBS, even if the normal-weight newborn was in total parenteral nutrition (TPN). It is known that TPN may present metabolic alterations, mainly for amino acids at NBS in MS/MS, frequently causing false positives. Actually, TPN is considered a special protocol in NBS, requiring several sample collections. In particular, a DBS sample is required before TPN, at basal time point (48 h after birth) and 72 h after the end of the procedure. In the case we report, even if the first DBS sample (before TPN) resulted negative, the repeated NBS tests revealed increased levels of Phe and dramatically high Phe/Tyr ratio. Thus, the newborn was recalled, and the NBS test was repeated several times before that HPA suspicion was confirmed by other specific biochemical tests. This case highlights the importance of Phe/Tyr ratio, only detectable by MS/MS analysis, in supporting the diagnostic suspicion during amino acids administration in the neonatal period.